Implementasi pendekatan kontekstual dalam bimbingan konseling untuk meningkatkan kecakapan berbahasa arab siswa MIN 3 malang - Ba’Abdullah, Adam; Mufidah, Nuril (Maliki Interdisciplinary Journal, 2025)
Arabic is a part of international languages that holds a significant and strategic position in strengthening various sectors, particularly in science and education. In the context of elementary education in Indonesia, Arabic plays a crucial role in shaping students’ language proficiency and character development. However, in practice, many students encounter challenges and obstacles in mastering the Arabic language, especially in the application of speaking skills.Through the application of a contextual approach in guidance and counseling services, the Arabic learning process can be transformed into a more meaningful and engaging experience. This approach emphasizes the connection between learning materials and students’ real-life experiences, thereby fostering greater emotional and motivational involvement. The results of this study indicate that after participating in contextual-based counseling sessions, fourth-grade students at MIN 3 Malang became more open in expressing their feelings and personal experiences. Furthermore, they found it easier to memorize vocabulary and were more active in practicing Arabic in daily life, both inside and outside the classroom. Thus, the contextual approach in guidance and counseling proves to be an effective strategy for improving Arabic language proficiency within the school environment.